2019
DOI: 10.1371/journal.pone.0210947
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of an e-learning course on patient safety: A controlled longitudinal study with medical students

Abstract: BackgroundTo improve patient safety, educational interventions on all system levels, including medical school are necessary. Sound theoretical knowledge on elements influencing patient safety (such as error management or team work) is the basis for behavioral changes of health care professionals.MethodsA controlled, quasi-experimental study with repeated measures was deployed. The intervention group participated in a mandatory e-learning course on patient safety (ELPAS) between October 2016 and December 2016. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
4
11
0
1
Order By: Relevance
“…The degree of improvement of the knowledge score of the experimental group was significantly higher compared with the control group in this study. This finding is consistent with a previous study that showed that e-learning interventions on patient safety significantly increased students' knowledge of patient safety compared to classroom lectures [16]. In addition, this finding supports other studies that used a single-group design and showed that e-learning diabetes education for school personnel significantly increased their knowledge of diabetes and maintained it for more than 12 months [17], and that web-based continuing education significantly increased nurses' knowledge of diabetes after their education [18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The degree of improvement of the knowledge score of the experimental group was significantly higher compared with the control group in this study. This finding is consistent with a previous study that showed that e-learning interventions on patient safety significantly increased students' knowledge of patient safety compared to classroom lectures [16]. In addition, this finding supports other studies that used a single-group design and showed that e-learning diabetes education for school personnel significantly increased their knowledge of diabetes and maintained it for more than 12 months [17], and that web-based continuing education significantly increased nurses' knowledge of diabetes after their education [18].…”
Section: Discussionsupporting
confidence: 92%
“…Such self-directed learning can be a useful educational strategy for busy clinical nurses [14] and is expected to be more cost-effective and repeatable than classroom lectures [15]. In previous studies, e-learning interventions improved student knowledge of patient safety compared to classroom instructional groups [16], increased nurses' confidence in caring for diabetic patients [17], and enhanced nurses' clinical competence in diabetes management [18]. However, an integrative review found that there was no significant difference in clinical performance compared to a control group [19], so it is necessary to compare and confirm the effect of anticancer drug treatment nursing education.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with much of the cross-sectional and longitudinal work investigating how virtual interventions (e.g. virtual simulations, games, e-learning) affect learning in higher education settings over time (Gaupp, Drazic, and Körner 2019;Hanus and Fox 2015;Madani et al 2014Madani et al , 2016. Figure 6.…”
Section: Summary and Discussionsupporting
confidence: 82%
“…Flexibility in e-learning means that the learning process can be implemented under the students' conditions, regardless of geographic location, which does not require a specific time or binding schedule, and it is easy to access the material. It is a significant benefit compared to conventional lecture methods [8,[10][11][12]. Based on research, 86.2% of students feel ready for an online learning model.…”
Section: Concentration and Online Learningmentioning
confidence: 99%